Exploring the environmental and social impacts of shrimp farming: A literature review in the Southern Coastal Region of Java - Andini, Lisa; Purwanto, Pratama Bimo; Kirana, Cininta Natya; Ulfani, Alamsyah; Riandika, Citra; Puteri, Telly Indi Cahyaning (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Shrimp farming in the southern coastal areas of Java has expanded rapidly due to increasing global demand, contributing significantly to local economic growth. However, this development has generated ecological degradation and social inequality, including water pollution, mangrove loss, and uneven resource distribution. Addressing these challenges requires balancing economic benefits with environmental and social sustainability. Methods: This study employed a qualitative literature review, analyzing five scientific sources on the impacts of shrimp farming on ecotourism, water quality, mangrove ecosystems, and socioeconomic conditions in Bantul, Kulon Progo, and Kebumen Regencies. Results: The analysis reveals that while shrimp farming enhances local incomes and can support ecotourism, unmanaged practices lead to ecosystem damage, water pollution, and heightened social disparities. Integrated management combining eco-friendly technologies, mangrove rehabilitation, waste treatment, and community empowerment is essential for sustainable development. Conclusion: Sustainable shrimp farming in Java’s coastal regions requires strict zoning, continuous monitoring, and policies that integrate environmental protection with community participation. Long-term development must prioritize economic productivity without sacrificing coastal ecosystem integrity. Novelty/Originality of this article: This study uniquely combines ecological and social perspectives, highlighting shrimp farming’s dual role.